PENGERING ENERGI SURYA UNTUK PENGERINGAN BAHAN PAKAIAN - Yuwana Yuwana; B. Sidebang; Evanila Silvia (DHARMA RAFLESIA, 2018)
This research based community service activity was conducted to solve the problem of clothes sun drying faced by students hosting in Orchid Dormitory, University of Bengkulu by introducing the further modified YSD-UNIB12 solar dryer. Strcture of dryer was 5 m x 6 m in size equipped with 2 m x 6 m drying cchamber having capacity of about 400 pieces of clothes. The dryer completed drying process of cloths made of nylon “sifón” and blouse in3 hours, and woolen cloth in 4 hours, and synthetical socks in 5 hours. The modified YSD- UNIB12 resulted better quality of dry cloth, saved time and space and minimised risk of clothes contamination. The dryer was successfully adopted by the dormitory management and inhabitants as very good solution of their their problem. Keywords: Solar energy dryer, clothes, dormitory